The origin of negative charging in amorphous Al2O3 films: the role of native defects. (12th March 2019) - Dicks, Oliver A; Cottom, Jonathon; Shluger, Alexander L; Afanas'ev, Valeri V
Abstract: Amorphous aluminum oxide Al2 O3 (a-Al2 O3 ) layers grown by various deposition techniques contain a significant density of negative charges. In spite of several experimental and theoretical studies, the origin of these charges still remains unclear. We report the results of extensive density functional theory calculations of native defects—O and Al vacancies and interstitials, as well as H interstitial centers—in different charge states in both crystalline α -Al2 O3 and in a-Al2 O3 . The results demonstrate that both the charging process and the energy distribution of traps responsible for negative charging of a-Al2 O3 films (Zahid et al 2010 IEEE Trans. Electron Devices 57 2907) can be understood assuming that the negatively charged Oi and VAl defects are nearly compensated by the positively charged Hi, VO and Ali defects in as prepared samples. Following electron injection, the states of Ali, VO or Hi in the band gap become occupied by electrons and sample becomes negatively charged. The optical excitation energies from these states into the oxide conduction band agree with the results of exhaustive photo-depopulation spectroscopy measurements (Zahid et al 2010 IEEE Trans. Electron Devices 57 2907). This new understanding of the origin of negative charging of a-Al2 O3 films is important for further development of nanoelectronic devices and solar cells.